Medium from mesangial cells incubated with aggregated IgA1 from IgA nephropathy patients reduces podocyte adhesion through activation of the renin angiotensin system (Swiss Medical Weekly, 2011)
BACKGROUND: Podocyte injury plays an important role in glomerulosclerosis in IgA nephropathy (IgAN), and detachment from the glomerular basement membrane is the main cause of podocyte damage. In a previous study we found that medium from mesangial cells incubated with aggregated IgA1 (aIgA1) isolated from IgAN patients decreased podocyte adhesive capacity. However, the underlying mechanism remains unclear. MATERIALS AND METHODS:Podocytes were incubated in medium from mesangial cells incubated with aIgA1 isolated from IgAN patients, enalaprilat (10–5 M) and chymostatin (20 μM), or with enalaprilat and chymostatin separately. Podocyte adhesive capacity was evaluated by cell counting and hexosaminidase assay. Expression of the renin angiotensin system was measured by real-time PCR, Western blot analysis and ELISA. RESULTS: Angiotensinogen, renin and angiotensin II type 1 and 2 receptors mRNA and protein expression, angiotensin-converting enzyme activity, and angiotensin II levels increased in podocyte lysates and conditioned culture media on exposure to mesangial medium containing aIgA1 from IgAN patients (P